Homestay re-visit implementation model based on spatial perspective in Langkawi Island / Zakaria Mat Arof, Tarmiji Masron and Noor Aniza Mat Ail - Mat Arof, Zakaria; Masron, Tarmiji; Mat Ail, Noor Aniza (Universiti Teknologi MARA, Perlis, 2014)
Homestay program is actively promoted as a community based tourism product in Malaysia. Officially, in 1995 this program was launched by Ministry of Culture, Arts and Tourism Malaysia in Temerloh, Pahang. This study was undertaken with the aim of investigating a practicing model of homestay management in Langkawi Island. Various variables of the communities’ participation and homestay management practices were identified, analysed and plotted. The field data survey was recorded in person and positioned by handheld GPS (Global Positioning System). Spatial and non-spatial data were processed through GIS (Geographic Information System). Various spatial integrations through GIS re-classing activities including neighbourhood, proximity and overlaying were carried out. The result displayed various perspectives of the existing homestay distribution in Langkawi. It is found that practicing model can be classified into three namely A, B and C. The paper also discusses the issue of participation, activities as well as distribution. The result could support the re-thinking of homestay location, management and program since it plays a very important role in the development of tourism in Langkawi Island that will ensure the economic sustainability among local communities.